On the optical performance of a spherical stationary reflector/tracking absorber solar collector - Rosa Christodoulaki; Panagiotis Tsekouras; Irene Koronaki (International Journal of Sustainable Energy, 2022)
The effect of specific design characteristics of the SRTA collector are discussed, such as the absorber diameter, the absorber length and the optical error from the tracking mechanism. It is found that the reduction of the absorber’s length by 29.6% leads to the reduction of the optical efficiency by about 13.7%. Increasing the absorber’s diameter is found to increase the optical efficiency, but only for diameters up to 0.05 m; further increase is found to have a negligible effect on the optical efficiency. The geometry of the studied collector is found to retain its high optical efficiency for optical errors up to 0.2o, but for higher optical errors lower efficiency is observed. This study shows that the SRTA solar concentrator can operate efficiently under a wide range of conditions and provides an insight for the design engineers of concentrated solar collectors.